The role of reelin in the development and evolution of the cerebral cortex - Tissir,F. (2002)
Reelin is an extracellular matrix protein that is defective in reeler mutant mice and plays a key role in the organization of architectonic patterns, particularly in the cerebral cortex. In mammals, a "reelin signal" is activated when reelin, secreted by Cajal-Retzius neurons, binds to receptors of the lipoprotein receptor family on the surface of cortical plate cells, and triggers Dab1 phosphorylation. As reelin is a key component of cortical development in mammals, comparative embryological studies of reelin expression were carried out during cortical development in non-mammalian amniotes (turtles, squamates, birds and crocodiles) in order to assess the putative role of reelin during cortical evolution. The data show that reelin is present in the cortical marginal zone in all amniotes, and suggest that reelin has been implicated in the evolution of the radial organization of the cortical plate in the synapsid lineage leading from stem amniotes to mammals, as well as in the lineage leading to squamates, thus providing an example of homoplastic evolution (evolutionary convergence). The mechanisms by which reelin instructs radial cortical organization in these two lineages seem different: in the synapsid lineage, a drastic amplification of reelin production occurred in Cajal-Retzius cells, whereas in squamates, in addition to reelin-secreting cells in the marginal zone, a second layer of reelin-producing cells developed in the subcortex. Altogether, our results suggest that the reelin-signaling pathway has played a significant role in shaping the evolution of cortical development.